2015
DOI: 10.1016/j.chom.2015.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Proteins Promote Repair of Endosomal Membranes Damaged by the Salmonella Type Three Secretion System 1

Abstract: Salmonella Typhimurium (S.Tm) is an enteropathogen requiring multiple virulence factors, including two type three secretion systems (T1 and T2). T1 triggers epithelium invasion in which the bacteria are taken up into endosomes that mature into Salmonella-containing vacuoles (SCV) and trigger T2 induction upon acidification. Mechanisms controlling endosome membrane integrity or pathogen egress into the cytosol are incompletely understood. We screened for host factors affecting invasion and SCV maturation and id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
123
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(133 citation statements)
references
References 72 publications
9
123
0
1
Order By: Relevance
“…A recent report provides evidence for a second role of autophagy in mediating sealing of the SCV membrane damaged by activity of the SPI1-T3SS, a phenomenon required for subsequent induction of the SPI2-T3SS. 33 Since we observed aggrephagy at the same extent in cells infected with wild-type and SPI1D strains (Fig. 7) and SPI2-T3SS is required for the formation of the LGP C aggresome (Fig.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…A recent report provides evidence for a second role of autophagy in mediating sealing of the SCV membrane damaged by activity of the SPI1-T3SS, a phenomenon required for subsequent induction of the SPI2-T3SS. 33 Since we observed aggrephagy at the same extent in cells infected with wild-type and SPI1D strains (Fig. 7) and SPI2-T3SS is required for the formation of the LGP C aggresome (Fig.…”
Section: Discussionmentioning
confidence: 63%
“…A recent report provided evidence for a role of autophagy in repairing some damaged phagosomes harboring S. Typhimurium. 33 Another study, however, showed that S. Typhimurium subverts autophagy to proliferate in the cytosol of epithelial cells. 19 The precise contribution of autophagy to the balance of the intraphagosomal and cytosolic bacterial populations coexisting in the epithelial cell remains not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…This enhanced state of autophagy likely contributes to the increased capacity of the MTMR4-depleted cells to eliminate intracellular Salmonella . Recent studies have made conflicting conclusions about the role of autophagy with regards to the intracellular viability of Salmonella (Yu et al, 2014; Kreibich et al, 2015). Using CFU assays to monitored viable bacteria 6 h post-infection, Yu et al (2014) observed decreased viability in HeLa cells when autophagy was inhibited using RNAi-depletion of LC3 while Kreibich et al (2015) observed elevated viable bacteria in autophagy impaired Atg5−/− MEFs.…”
Section: Discussionmentioning
confidence: 99%
“…These signals recruit essential anti-bacterial autophagy components including several cargo receptors, the kinase TBK1 and WIPI2, that restrict Salmonella proliferation (Radtke et al, 2007;Thurston et al, 2016Thurston et al, , 2009Thurston et al, , 2012. Autophagy has also a role in sealing damaged endosomal membranes, allowing T3SS2 induction inside the SCV (Kreibich et al, 2015;Owen and Casanova, 2015). In epithelial cells, Salmonella induces the formation of ubiquitinated aggregates near the SCV in a T3SS2-dependent manner.…”
Section: Autophagymentioning
confidence: 99%